Literature Review Dampak Artificial Intelligence terhadap Peningkatan Kualitas Perawatan Pasien - Bagus Alfrisa; Muhammad Reza Fahlevi Hanafi; Yuni Suharnida Lubis (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The integration of telemedicine and artificial intelligence (AI) into critical care has emerged as a revolutionary development in the healthcare sector, aiming to enhance patient care and outcomes. This research aims to explore the impact of these technologies on improving the quality of patient care in intensive care units (ICUs). A systematic review of recent studies published between 2018 and 2023 was conducted to analyze the role of telemedicine in improving access to healthcare and the application of AI in enhancing diagnostic accuracy and monitoring patients in real-time. The findings suggest that both telemedicine and AI significantly reduce response times, improve decision-making processes, and increase the accuracy of diagnoses, which ultimately contribute to better patient safety and outcomes. The research also highlights challenges, including infrastructure limitations and the need for specialized training for healthcare professionals. The study’s implications underline the importance of integrating these technologies in critical care units to improve overall healthcare delivery, while addressing barriers to implementation. Future research should focus on overcoming these challenges and exploring long-term outcomes of technology use in critical care environments.